Communication Strategies and Election Outcome: An examination of Nigerian Gubernatorial Elections - Koech, Daniel Kibet; Akinyemi-Oke, Alaba Victoria; Okoye, Innocent E.; Molnár, Edina (Journal of Posthumanism, 2025)
Communication plays a vital role in Nigerian political campaigns, making it crucial to regularly assess the different strategies employed by parties and candidates to understand how they influence electoral success. This research explores the impact of political communication strategies on voters’ decisions in Nigerian gubernatorial elections. Using the Persuasion Theory (AIDA Model) as a framework, the study conducts a cross-sectional survey involving 2,942,447 registered voters, with a sample of 400 respondents, to analyze how politicians effectively engage and mobilize voters to secure electoral victories. The results from correlation and hypothesis testing reveal significant links between candidates’ communication tools and strategies and voters’ awareness, attitudes, and voting choices. The study highlights that an integrated approach—combining social media, traditional media, rallies, and personal endorsements—is key to successful political mobilization and voter engagement.